Fish Control Process and Traceability for Value Creation Using Blockchain Technology - Ferreira, J.; Martins, A.; Tokkozhina, U.; Helgheim, B. (Confernece in Innovations in Bio-Inspired Computing and Applications, 2022)
Currently, the globe and, more specifically, corporate processes are evolving towards digitization and the elimination of time-consuming procedures. As origin knowledge and safety assurance of products became more important in establishing end-consumer confidence, traceability solutions are acute. A Blockchain (BC) is one of the most exciting disruptive technologies emerging today. The purpose of this study is to analyze the possibility of using BC to allow end-to-end supply chain (SC) management traceability and to provide a proposition of a BC application for fish tracking and control in SC contexts. The proposition demonstrates that BC provides the use of a single information system by several players across SC, resulting in more secure and efficient data sharing. A future understanding of the significance of BC technology usage as a traceability supplier and a detailed testing of a proposed architecture is identified as a diretion for future study. We, therefore, study current applications in supply chain management, with a big emphasis on the fish control process.